ANATOMICAL AND PHYSICAL AGE CHARACTERISTICS OF CHILDREN AGED 7-10 YEARS - Utarbaeva Aynura Amanjolovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article presents the anatomical and physical age characteristics of the body of children 7-9 years old.